VIBRATION TESTS AND PROTECTION OF BEARING STRUCTURES IN ELECTRONIC PACKAGES ON VARIOUS LEVELS OF COMPLEXITY - KOVTUN, IHOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper is aimed at developing approach for vibration analysis for structurally complex electronic packages, which considers motion of mass relative to vibration base as absolute motion of this mass relative to stationary base in oscillatory system where mass is set on base through elastic and dissipative joint, what demonstrated, in general, impossible using external vibration to assess internal vibration of researched structures and was experimentally verified by simultaneous application of methods for vibrometry, electrotensometry and high-speed video-shooting. Paper also represents theory and practice for effective protection of circuit cards from dynamic forces by creating or modifying elastic and dissipative mechanical joints between structural elements of bearing structures in electronic packages on various levels of complexity, which become links of deformation transmission as inside so outside of these structures. Analysis of elastic and dissipative parameters effect on vibration activity of circuit cards on various levels of package complexity revealed that constructional damping bearing structures, produced by dry external friction due to opposite displacement of contacting surfaces, surpasses viscous internal friction in materials of structural parts and components of electronic packages. Method for reducing dynamic stress and deflection in critical section of circuit cards in resonance condition has been developed by embedding elastic and dissipation joint introduced by dry friction damper whose stiffness is directly proportional to generalized elastic resistance force, which is the net force for pressure and friction on the contact surface in kinematic pair engaging oscillation, and which, increasing, with increasing vibration amplitude, provides reducing dynamic stress and deflection transmitted to circuit cards. The mathematical model provides calculation of minimally acceptable stiffness and specification of construction parameters for the dry friction damper introduced by semi-elliptical beam with rectangular section profile.